086 Sleep midpoint after job loss predicts breakfast skipping patterns. (3rd May 2021) - Callovini, Leah; Gubka, Gaby; Mayer, Candace; Rojo-Wissar, Darlynn; Glickenstein, David; Thomson, Cynthia; Quan, Stuart; Silva, Graciela; Haynes, Patricia
Abstract: Introduction: Few studies have examined circadian phase after job loss, an event that upends daily routine. It is common that a daily routine begins with the consumption of breakfast, and breakfast behavior may contribute to health status in adults. Therefore, we sought to examine whether a later midpoint of sleep was associated with breakfast skipping among adults whose schedules were no longer dictated by employment. Methods: Data were obtained from the Assessing Daily Activity Patterns Through Occupational Transitions (ADAPT) study. The sample of 155 participants had involuntarily lost their jobs in the last 90 days. Both cross-sectional and 18-month longitudinal analyses assessed the relationship between sleep midpoint after job loss and current and later breakfast skipping. Assessment periods were 14 days. Sleep was measured via actigraphy, and breakfast skipping was measured via daily diary (1 = had breakfast; 0 = did not have breakfast). The midpoint of sleep was calculated as the circular center based on actigraphy sleep onset and offset times. Results: The midpoint of sleep at baseline was negatively associated with breakfast consumption at baseline (B = -.09, SE = .02, p = .000). Also, a later midpoint was associated with breakfast skipping over the next 18 months (estimate = -.08; SE = .02; p = .000). Prospective findings remained significant when adjusting for gender, ethnicity, age, perceived stress, body mass index (BMI), education, and reemployment over time. Education (estimate = 14.26, SE = 6.23, p < .05) and BMI (estimate = -.51, SE = .25, p < .05) were the only significant covariates. No other sleep indices predicted breakfast behavior cross-sectionally or prospectively. Conclusion: Consistent with research in adolescents, unemployed adults with a later circadian phase are more likely to skip breakfast more often. Breakfast skipping was also associated with higher BMI. Taken together, these findings provide support for the future testing of sleep/wake scheduling interventions to modify breakfast skipping and potentially mitigate weight gain after job loss. Support (if any): #1R01HL117995-01A1